Nilai Kejujuran sebagai Identitas Moral Bangsa di Tengah Arus Matrealisme Global - Aeni Latifah; Neng Lailatul Faaizah; Syifa Aqmaliyah (Lembaga Pengembangan Kinerja Dosen, 2026)
Honesty (ṣidq) is a fundamental moral value in Islam that serves as the foundation for personal integrity and social ethics. In the current era of globalization and growing materialistic culture, this value faces serious challenges as societal orientation shifts from moral virtue to economic achievement and social image. This study employs a narrative review method, analyzing recent literature on moral education, Islamic ethics, and contemporary social dynamics. The findings reveal that honesty functions not only as a personal virtue but also as a social force that strengthens public trust and national stability. However, the global wave of materialism has weakened the internalization of ṣidq, especially among younger generations. Restoring honesty as the moral identity of the nation requires synergy among character-based education, spiritual reinforcement, and public policies that promote transparency and integrity. The recontextualization of honesty through Islamic spiritual principles and Rokeach’s value theory offers a path toward moral recovery for Indonesian society amid the global challenges of the 21st century.